2022
DOI: 10.21203/rs.3.rs-1649062/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aetiology and clinical characteristics of psoas abscesses in China, 2011-2021: A retrospective study

Abstract: Psoas abscess (PA) is an uncommon disease that has been increasingly reported in recent years. We reviewed patients with PA and analysed their clinical characteristics to improve the understanding of this rare disorder. The study retrospectively reviewed the clinical presentations, microbiology, and outcomes of patients with PA between 2011 and 2021 in Zhejiang Provincial People’s Hospital in China. There were 35 cases out of 23057427 hospitalised adult patients; the mean age was 60 years, and 65.7% of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Only 190 patients had their gender described, and 103 males and 87 females were evaluated at a mean follow-up of 23.5 months. Twelve studies used CT-guided PD [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], seven studies used US-guided PD [ 12 , 36 , 37 , 38 , 39 , 40 , 41 ], and two studies used both CT-guided and US-guided PD [ 42 , 43 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 190 patients had their gender described, and 103 males and 87 females were evaluated at a mean follow-up of 23.5 months. Twelve studies used CT-guided PD [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], seven studies used US-guided PD [ 12 , 36 , 37 , 38 , 39 , 40 , 41 ], and two studies used both CT-guided and US-guided PD [ 42 , 43 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported using US-guided PD in 137 patients [ 12 , 36 , 37 , 38 , 39 , 40 , 41 ]. Among these, one study was conducted prospectively [ 37 ], and six studies were conducted retrospectively [ 12 , 36 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations